Ultrasound-guided needle release of the transverse carpal ligament with and without corticosteroid injection for the treatment of carpal tunnel syndrome - Guo, Xuan-Yan (J Orthop Surg Res, 2018)
BACKGROUND: To compare the clinical effectiveness of ultrasound-guided needle release of the transverse carpal ligament (TCL) with and without corticosteroid injection in carpal tunnel syndrome (CTS). METHODS: From June 2016 to June 2017, 49 CTS patients (50 wrists) were included in this study. Twenty-five wrists were treated with ultrasound-guided needle release of the TCL plus corticosteroid injection (group A), and 25 wrists were treated with single ultrasound-guided needle release of the TCL (group B). The following parameters were assessed and compared including postprocedure results according to relief of symptoms, ultrasound parameters (cross-sectional area of the median nerve at the levels of pisiform, flattening ratio of median nerve at the levels of the hamate bone, and the thicknesses of TCL on the cross-section at the level of the hamate bone), and electrophysiological parameters (distal motor latency and sensory conduction velocity). RESULTS: Group A had higher overall excellent and good rate 3 months after the procedure than group B (84 vs 52%, P < 0.05). There were significant differences regarding the above ultrasonic and electrophysiological parameters between the baseline and postprocedure values in both groups (all P < 0.05). There were significant differences regarding the postprocedure values of above ultrasonic and electrophysiological parameters between the two groups (all P < 0.05). No complications such as infection or tendon rupture were noted. No procedures were converted to the open release. CONCLUSIONS: Both techniques are effective in treating CTS. Ultrasound-guided needle release of the TCL with corticosteroid injection had better treatment benefits than single ultrasound-guided needle release of the TCL in treating CTS.